THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CONSUMER LOYALTY THROUGH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE IN PURCHASING POCARI SWEAT PRODUCTS - Allaitsi, Haula; Pakarti, Piji; Anomsari, Ariati; Oktavia, Vicky (Universitas Islam Lamongan, 2024)
This research was conducted to determine the effect of product quality and price on consumer loyalty through consumer satisfaction. This research used a quantitative method with a purposive sampling technique (sampling with criteria) with a total of 150 respondents and involved a population of teenagers and adults with a minimum age of 17 years, who had purchased and consumed Pocari Sweat at least twice, with the object being Dian Nuswantoro University students. This test uses primary data using a questionnaire. The data analysis technique uses PLS-SEM. The research results show that product quality and price have a positive effect on consumer satisfaction, product quality has a positive effect on consumer loyalty, consumer satisfaction has a positive effect on consumer loyalty, while price has no effect on consumer loyalty.